1947
DOI: 10.1099/00221287-1-2-232
|View full text |Cite
|
Sign up to set email alerts
|

The Routine Examination for Antibiotics Produced by Moulds

Abstract: SUMMARY:From the existing methods for identifying common antibiotics it is possible to select tests for recognizing one or more of fourteen known antibiotics in crude culture medium. These tests, given in tabular form, are : (1) stability at pH 2.0 and 9.5; (2) ether-water partition at pH 2-0, 6.0-7.0 and 9.0; and (3) relative activity towards specified strains of Staphylococcus aureus and Bacterium coli. Further tests depend on destruction of penicillin by penicillinase, colour reactions, and volatility of as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1956
1956
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…Of the 3 processes mentioned thus far, this is by far the least effective. Repeated studies have shown that, while unstable at high pH (McCallum and others 2002), patulin is relatively stable to thermal degradation in the pH range of 3.5 to 5.5, with lower pH leading to greater stability (Heatley and Philpot 1947;Lovett and Peeler 1973). The half-life of patulin held at 25 °C at pH 6.0 and 8.0 has been shown to be 55 and 2.6 d, respectively (Brackett and Marth 1979c).…”
Section: Control During Productionmentioning
confidence: 99%
“…Of the 3 processes mentioned thus far, this is by far the least effective. Repeated studies have shown that, while unstable at high pH (McCallum and others 2002), patulin is relatively stable to thermal degradation in the pH range of 3.5 to 5.5, with lower pH leading to greater stability (Heatley and Philpot 1947;Lovett and Peeler 1973). The half-life of patulin held at 25 °C at pH 6.0 and 8.0 has been shown to be 55 and 2.6 d, respectively (Brackett and Marth 1979c).…”
Section: Control During Productionmentioning
confidence: 99%
“…Of the three processes mentioned thus far, this is by far the least effective. Repeated studies have shown that, while unstable at high pH [46], patulin is relatively stable to thermal degradation in the pH range of 3.5 to 5.5, with lower pH leading to greater stability [225,226]. The half-life of patulin held at 25 °C at pH 6.0 and 8.0 has been shown to be 55 and 2.6 days respectively [227].…”
Section: During Juice Production: Preparation For Crushing Filteringmentioning
confidence: 99%
“…The heat stability of this mycotoxin was first reported by Wiesner (1942) in aqueous solution. Heatley & Philpot (1947) subsequently reported that PAT was stable to a heat treatment of 100°C/15 min at pH 2.0 in a model system. Scott & Somers (1968) reported that the heating of apple juice containing added vitamin C (ascorbic acid) (35 mg/100 mL) at 80°C for 30 min for 10 and 20 min caused a reduction in the initial amount of PAT (200 lg) of 45% (90 lg) and 55% (110 lg), respectively.…”
Section: First Pasteurizationmentioning
confidence: 97%